‘URF’ DALAM PERNIKAHAN ADAT BANJAR PERSPEKTIF ABDUL WAHAB KHALLAF: 'URF' IN BANJAR CUSTOM MARRIAGE PERSPECTIVE ABDUL WAHAB KHALLAF - Jinan, Muhammad Sakinul; Hidayah, Mahroji; Wardah, Safiah (Mitsaqan Ghalizan, 2023)
The procession of the wedding ceremony is a ritual that has become a custom in the Banjar community. There are several stages in marriage in the Banjar community, such as basuluh, dadang, bapaayuan, baantar patalian, balarangan, bamandi-mandi, batamat Qur'an, prostration and bailangan. However, in Banjar custom at each stage there are symbols, tools and beliefs that are believed to protect the bride and groom, sometimes there are even tools, symbols and beliefs that are considered to deviate from religious rules and if not implemented can result in negative things for the bride and groom. But in taking (Istinbath) customary Islamic law can be used as a proposition or a method known as Urf. The traditional Banjar wedding procession cannot be separated from custom, so this article looks at adat from the perspective of banjar marriage in taking law through urf by looking at the perspective of Abdul Wahab Khallaf.